Impact of Disaster on Underprivileged Children in Covid-19 Pandemic: Policy Response for Emergency Education - Mukherjee, Mrinal; Maity, Chanchal; Chatterjee, Somdutta (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
It is necessary to recognize and address the differential impact of disasters on society. It is quite possible that a significant number of children to become victims of the COVID-19 caused social disaster. As a result, there would be an increase in the number of school dropouts and child labor, which indicates a substantial number of children will be deprived of their right to education. Any alternative response during school closure, like internet-based remote teaching learning, might not compensate the loss of learning as nearly half of the world is without access to the internet.